Effect of Compudose on grazing steers in pasture, then in feedlot - Corah, L.; Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station, 2011)
Steers implanted with an estradiol removable implant (Compudose) gained 14.8% faster during 121 days of grazing and 12.1% faster in the feedlot than control steers not implanted. Implanting improved feed efficiency 6.9% during finishing. Removing implants after grazing resulted in slowest and least efficient feedlot gains. Steers implanted only during the finishing phase gained the fastest and most efficiently in feedlot. Results of this 240-day test indicate that one implant stimulates performance at least 240 days
Keywords: Beef; Steers; Performance; Implants; Feed efficiency